8 - When Is ‘Techno-talk’ a Fatal Distraction? ICT in Contemporary Development Discourse on Africa - Adesina, Jimi O. (Africa Development, 2006)
The last two-and-half decades have seen a resurgence of neo-modernisation thinking, which is most evident in the imageries of modernity that infuse the dominant contemporary development discourse on Africa. The discussion on Information and Communication Technology (ICT) has become a signifier of that development mindset and the alleged solution to Africa’s development problems. In this paper, we argue that while ICT offers tremendous potentials, its use in the current dominant development discourse tends to confuse the appearance of things with their essence. It fails to address the multidimensional nature of the development crisis and impediments that have developed in the last twenty-five years, and is in danger of reproducing elements of perverse growth identified in first two decades of post-colonial development experience. In failing to address how twenty-five years of neoliberal vivisectomy compounded Africa’s development crisis, the ICT techno-talk is in danger of becoming a distraction. It becomes a fatal distraction where its discourse diverts attention from the key elements of this vivisection and its consequences. Fundamental to rethinking Africa’s development, the paper argues, is connecting the dots: the relationship between development crisis and debt peonage, aid-dependency, the retreat from the public (social) policy domain, and the dissonance between the regional development objectives and current trade regimes. Critical to sus- tainable ICT, specifically, and development broadly is reinventing the public domain. We use the state of higher education on the continent to illustrate this, and the imperative of endogeneity.